Population genetic structure of Malayan Tapir (Tapirus indicus Desmarest) in Peninsular Malaysia - Lim, Qi Luan (2019)
The Malayan tapir (Tapirus indicus Desmarest) is an endangered fauna listed in the International Union for Conservation of Nature (IUCN) Red List with estimated population size at less than 2,000 individuals in Peninsular Malaysia. Despite the existing conservation programme and ecological information about this species, the population genetic structure of the Malayan tapir in Peninsular Malaysia is still not well-known, largely due to a lack of available genetic markers. The lack of such information may impede the on-going efforts for its conservation and management. The works presented here aimed to develop genetic markers for the investigation of population genetic structure of the Malayan tapir in Peninsular Malaysia. Forty-one microsatellite markers comprising of seven random amplified microsatellite (RAM)-isolated and 34 cross-amplification microsatellite markers, obtained from literature and National Center for Biotechnology Information (NCBI) database, were screened with polymerase chain reaction (PCR), sequencing and fragment analysis in 67 Malayan tapirs. Eight polymorphic markers were successfully developed and used in the population genetic structure analysis. Using K-means clustering algorithm, five clusters were inferred among the wild samples (N = 57), which showed a complex population structure probably comprising multiple continuous populations that also experiencing considerably restricted gene flow due to isolation by geographical barriers especially mountain ranges. Mitochondrial control region sequences in Peninsular Malaysia samples (N = 44; including two samples from Singapore Zoo) revealed two clades that might be established during the late Pleistocene. One of the clades was exclusive in Peninsular Malaysia samples in comparison with the Thailand samples from a previous study. However, the geographical distribution of the clades did not show a clear population structure. A total of 12 novel haplotypes were detected. Both the markers suggested low to moderate genetic diversity in the Malayan tapir studied. In addition, a universal sex-typing method based on the sex determining region Y and zinc finger gene (as positive control) was tested. A preliminary assessment of sex ratio was conducted using the data extracted from the tapir datasheets obtained from the Department of Wildlife and National Parks, Sungai Dusun Wildlife Conservation Centre and Zoo Negara; and aided with the developed sex-typing marker for those biological samples with unknown sex. Overall, there was no significant bias towards either sex. Nevertheless, in the wild-born tapirs, the sex ratio seemed to favour females and the opposite was observed in the captive-born tapirs. From 2004 to 2015, there seemed to be an increase in the male proportion but no extreme ratio was found. Combined with microsatellite data, there was no sex-biased dispersal detected in a spatial autocorrelation analysis that might shape the population structure of the Malayan tapir observed. A major limitation in all these studies was the sampling bias where, across Peninsular Malaysia, more samples were sampled from the Selangor-Negeri Sembilan-Pahang regions and only a few were representatives of the populations from the north forest complexes.